Women’s involvement in intra-household decision-making and infant and young child feeding practices in Central Asia - Abdurazzakova, Dilnovoz; Kosec, Katrina; Parpievd, Ziyodullo (Elsevier, 2024)
This paper examines the relationship between women’s empowerment and infant and young child feeding practices in Central Asia using Demographic and Health Survey datasets collected during 1995–2017. We employ a measure of women’s empowerment with three dimensions that is available for many recent surveys as well as a measure of decision-making power over use of one’s own income present for income-earning mothers in all surveys. We identify a positive association between a woman’s decision-making power—a measure of her instrumental agency—and adherence to World Health Organization–recommended feeding practices. We find little significant association between a woman’s attitude toward domestic violence, or her degree of social independence, and adherence to recommended feeding practices. Our results further show that the association between women’s decision-making power and feeding practices varies little with child gender, whether or not she cohabitates with her mother-in-law, or household wealth. We thus provide evidence from Central Asia that policies and programs intended to empower women can improve child feeding practices, with similar benefits across a variety of household types.